(untitled) (Mongolian Journal of Humanities and Social Sciences, 2023)
How long has press photography developed in Mongolia, some of the measures taken to develop it, how it has developed, and the current situation will be briefly discussed. Having Mongolian photojournalists At the national level, it has been developing as a type of photojournalistic activity since the middle of 1940. Since then, the daily newspapers "Unen", "Höldölmör", "Zaluchuudyn Unen", "Pioneer’s Unen", "Ulaanbaatar News", "Literature Art", "Ulaan Od", "Ekh orny Manaa" newspapers, "Modern Mongolia", "Science and life" magazine, State Photo and MONCAME agency have many photojournalists and photo reporters working. By the 1970s, the photography report type had been steadily developed and photographs, photo news, reports, and portraits taken by our first photographers were published regularly. Issue of phasing of the development of photojournalism in Mongolia. In this study, the development of Mongolian photography, especially the history of photojournalism is reviewed in phases as follows: The beginning of photojournalism in Mongolia - 1940 - early 1960s. The period of development of Mongolian professional photojournalism - from 1980 to 1990 Photojournalism of market and social transition period – 1990-2010, From 2011 until now, as "Digital or modern photojournalism". Thus, the photojournalism development can be reviewed in 5 phases. We considered in addition to the development of photography technology, the time when professional photographers appeared. As for today, the role of photography in the media is increasingly decorating the appearance of newspapers, and the quality of the information delivered to the readers is becoming a unique pattern. Монголын хэвлэлийн гэрэл зургийн түүхэн хөгжил Хураангуй: Монголд хэвлэлийн гэрэл зураг хэдий үеэс үүсэж хөгжсөн, түүнийг хөгжүүлэх талаар авч хэрэгжүүлсэн зарим арга хэмжээ, хэрхэн хөгжиж ирсэн чиг хандлага, одоогийн нөхцөл байдлын талаар товч авч үзэх юм. Монголд анх гэрэл зураг хөгжсөн нь хэвлэл мэдээллийн гэрэл зураг, гэрэл зургийн сэтгүүл зүй хөгжих үндэс болсон бөгөөд үндэсний гэрэл зургийн сэтгүүлчид төрж, мэргэжлийн төвшинд хөгжүүлэх талаар төр, засгаас авч хэрэгжүүлсэн олон талт арга хэмжээний үр дүнд тусгайлсан мэргэжлийн гэрэл зургийн сэтгүүлчдийг гадаадын их, дээд сургуульд сургаж, дээд боловсрол эзэмшүүлж байжээ. Фото сэтгүүл зүйд залуу үе түрэн гарч ирэхийн зэрэгцээ тодорхой төрөл, сэдэв, чиглэлүүдээр дагнасан сайн дурын клуб, бүлэг, нийгэмлэг, агентлаг болон ажиллаж байгаа нь гэрэл зургийн сэтгүүл зүйн хөгжлийн мөн нэгэн хэлбэр гэж болно. Өдөр тутмын сонин, сэтгүүлүүд болон хэвлэл мэдээллийн хэрэгслүүд өөрийн редакцадаа /зарим нь редакцтай эсэхэд эргэлзээтэй/ гэрэл зургийн редактор байтугай сурвалжлагч, гэрэл зурагчингүй ажилладаг. Олонх нь интернэтээс зургаа авч байгаа нь энэ цагийн гэрэл зургийн сэтгүүл зүйн хөгжилд ухралт болдог. Гэвч хөгжил дэвшилд дамжих, туулах ёстой “тийм” цаг үе, зүй тогтол гэж бий гэдэг. Цаашид бид гэрэл зургийн сэтгүүл зүйн хөгжлийг үечилж, тухайн үеийн байдал, өнөөгийн төвшинд хүрэхэд хэрхэн нөлөөлсөн талаар нарийвчлан судлах хэрэгцээ энэ салбарт бий. Түлхүүр үг: Фото сэтгүүл зүй, түүхэн фото, фото зургийн хөгжил